Congenital Erythropoietic Porphyria - A Report Of Two Cases - Das Jayasri; Sarkar Jyotirindra Nath; Roy Aloke Kumar (Wolters Kluwer Medknow Publications, 2002)
Two classical cases of congenital eryhropoietic porphria, a rare autosomal dominant disorder, are described.